Using the Molecular Classification of Glioblastoma to Inform Personalized Treatment - Olar, Adriana (2014)
Glioblastoma is the most common and most aggressive diffuse glioma, associated with short survival and uniformly fatal outcome irrespective of treatment. It is characterized by morphologic, genetic, and gene-expression heterogeneity. The current standard of treatment is maximal surgical resection, followed by radiation, with concurrent and adjuvant chemotherapy. Due to the heterogeneity most tumors develop resistance to treatment and shortly recur. Following recurrence glioblastoma is quickly fatal in the majority of cases. Recent genetic molecular advances have contributed to a better understanding of glioblastoma pathophysiology and disease stratification. In this paper we review the basic glioblastoma pathophysiology with emphasis on clinically relevant genetic molecular alterations and potential targets for further drug development.